Pelatihan Pemanfaatan E-Learning Berbasis Website Bagi Guru Pendidikan Teknik Otomotif Di Kota Kupang - Priyono, Priyono; Suprapto, Edy; Fahrizal, Fahrizal; K, Basri (Jurnal Ilmiah Mandala Education (JIME), 2021)
The change in learning models from conventional to online due to the impact of the COVID-19 pandemic has changed the way of thinking, methods used, paradigms and learning approaches that prioritize independent learning online with internet facilities. Through the internet all information is available, but it still has to be shared and sorted according to the needs and information to be taught to students. For this reason, competent teachers are needed, not only pedagogically, socially and professionally, but also required to master learning technology. This training is conducted to train teachers in planning, designing, developing and operating webside-based e-learning in the learning process that will be carried out with their students. The training method is designed with an online training and face-to-face approach. The approach uses hands-on exercises, tutorials and follow-up consultations. The results of the training showed an increase in the knowledge and skills of teachers about learning media. Before the training, the average understanding of teachers about learning media got a value of 52, while after being given training it became 84. Then seen from the skills of making media, before training teachers could not create website-based media, but after being given training teachers could create and develop media webside based learning.